A Novel Approach for Deriving Force Field Torsion Angle Parameters Accounting for Conformation-Dependent Solvation Effects - Zgarbová, Marie; Luque, F Javier; Šponer, Jiří; Otyepka, Michal; Jurečka, Petr (Journal of chemical theory and computation, 2012)
A procedure for deriving force field torsion parameters including certain previously neglected solvation effects is suggested. In contrast to the conventional in vacuo approaches, the dihedral parameters are obtained from the difference between the quantum-mechanical self-consistent reaction field and Poisson-Boltzmann continuum solvation models. An analysis of the solvation contributions shows that two major effects neglected when torsion parameters are derived in vacuo are (i) conformation-dependent solute polarization and (ii) solvation of conformation-dependent charge distribution. Using the glycosidic torsion as an example, we demonstrate that the corresponding correction for the torsion potential is substantial and important. Our approach avoids double counting of solvation effects and provides parameters that may be used in combination with any of the widely used nonpolarizable discrete solvent models, such as TIPnP or SPC/E, or with continuum solvent models. Differences between our model and the previously suggested solvation models are discussed. Improvements were demonstrated for the latest AMBER RNA χOL3 parameters derived with inclusion of solvent effects in a previous publication (Zgarbova et al. J. Chem. Theory Comput.2011, 7, 2886). The described procedure may help to provide consistently better force field parameters than the currently used parametrization approaches.